Experimental Investigation of Solar Room Heater for Commercial Purpose - Singh, Vineet; R. Mishra, V; Nigam, Akash; Kumar, Niraj; Mahewari, Anurag; Kushwaha, Saurabh (International Journal of Engineering and Technology, 2018)
According to the present era the requirement of the energy is continuously increasing. At the earth surface abundant quantity of heat is available but not in useful form, one of the main source of this energy is Solar which is available free of cost. On the basis of this theory we have designed a solar room heater by using tin cans soldered with spiral wire for increasing heat transfer between air and solar heat present in the collector. After designing the experimental set up experiment will be carried out for finding the outlet temperature, velocity of air for calculating heat transfer and pressure drop, heat transfer characteristics across the solar air heater. In this study, we have concluded the temperature of inlet air will improve around 170C to 200C without using any external device like blower and fans.Â